Draft Annual Plan (2008-09) (Scheme-Wise Details) Volume - 2 Union Territory of Puducherry - Planning Commission (Planning Commission, 2008)
The Union Territory of Pondicherry is an Industrially backward area classified as Category-A, Special District. Due to the pro-active investment policies, hassle free environment and industry friendly Administration, the Union Territory has made rapid strides in industrialization. There are 71 Large Scale, 169 Medium Scale and 7681 Small Scale and Micro Industries available with an investment of Rs.2156.41 Crores and providing employment to 92,087 persons. During the X Plan period, 25 LSI, 35 MSI and 940 SSI have been set up with an investment of Rs.610.74 Crores providing employment to 11468 persons. The Industrial Guidance Bureau networking the licensing and clearing agencies has been established to help the entrepreneurs to set up their units expeditiously. the Pondicherry Industrial Promotion Development and Investment Corporation (PIPDIC), a state owned Finance Corporation has been playing a catalytic role in the industrial development.
Government of Puducherry Planning and Research Department